Chiral Lewis Acids - Mikami, Koichi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
The series Topics in Organometallic Chemistry presents critical overviews of research results in organometallic chemistry. As our understanding of organometallic structure, properties and mechanisms increases, new ways are opened for the design of organometallic compounds and reactions tailored to the needs of such diverse areas as organic synthesis, medical research, biology and materials science. Thus the scope of coverage includes a broad range of topics of pure and applied organometallic chemistry, where new breakthroughs are being achieved that are of significance to a larger scientific audience. The individual volumes of Topics in Organometallic Chemistry are thematic. Review articles are generally invited by the volume editors. All chapters from Topics in Organometallic Chemistry are published OnlineFirst with an individual DOI. In references, Topics in Organometallic Chemistry is abbreviated as Top Organomet Chem and cited as a journal.
Chiral Fluorous Lewis Acid Complexes -- Chiral Lewis & Broensted Acids -- Organocatalysts combined with Chiral Lewis Acid Complexes -- Hybrid Ligands for Chiral Lewis Acids -- Chirality in Lewis Acid Complexes -- Chiral Bimetallic Lewis Acids -- Chiral Alkali Earth Complexes -- Broensted Acid/Lewis Base Hybrid Complexes -- Chiral Lewis Acids for Alder Ene & Diels-Alder reactions -- Chiral Lewis Acids in Surface -- The Future of Chiral Lewis Acids -- Carbophilic Gold Lewis Acid Complexes.
Keywords: Organometallic chemistry .; Catalysis; Inorganic chemistry; Organometallic Chemistry; Catalysis; Inorganic Chemistry